Applying an Extended Theory of Planned Behaviour Model to Predict Students’ University Intentions: A Structural Equation Model - Cooper, Grant; Barkatsas, Tasos (Brill, 2023)
The benefits of higher education include increased employment rates, higher average salaries; increased social status and typically better economic security. If universityparticipation is to increase, understanding students’ university motivations in the 21st century is crucial. Poorly targeted stakeholder interventions are less likely to result in desired change and at the same time cost relatively large sums of money. The purpose of this article is to further our understanding of the psychosocial predictors of students’ intentions to enrol at university. Using an extended Theory of Planned Behaviour model, 252 Year 12 students from Victoria, Australia completed a self-report survey questionnaire. The results indicated that attitude and subjective norm were significant predictors of students’ university intentions. Collectively, these results have both practical implications for how stakeholders promote university participation and theoretical consequences for how researchers predict students’ intentions. The findings of this study can be used to inform policies or interventions associated with students’ participation in higher education.